Phenomenology of keV scale sterile neutrino dark matter with S4 flavor symmetry - Nayana Gautam; Mrinal Kumar Das (Journal of High Energy Physics)
Abstract We study the possibility of simultaneously addressing neutrino phenomenology and the dark matter in the framework of inverse seesaw. The model is the extension of the standard model by the addition of two right handed neutrinos and three sterile fermions which leads to a light sterile state with the mass in the keV range along with three light active neutrino states. The lightest sterile neutrino can account for a feasible dark matter (DM) candidate. We present a S4 flavor symmetric model which is further augmented by Z4 × Z3 symmetry to constrain the Yukawa Lagrangian. The structures of the mass matrices involved in inverse seesaw within the S4 framework naturally give rise to correct neutrino mass matrix with non-zero reactor mixing angle θ13. In this framework, we conduct a detailed numerical analysis both for normal hierarchy as well as inverted hierarchy to obtain dark matter mass and DM-active mixing which are the key factors for considering sterile neutrino as a viable dark matter candidate. We constrain the parameter space of the model from the latest cosmological bounds on the mass of the dark matter and DM-active mixing.